DIFFERENCE IN STATE OF NUTRITION BETWEEN ACTIVE AND NON ACTIVE WOMEN - Mladenović Ivana; Nikolić Maja (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Modern sedentary women's live, phisical inactivity, put off matrninity for later are the majority bad factors for women halty and working capacity . The main target of this work is to show difference in anthropometrical characteristics and state of nutrition women athlets and women non-athlets average ages of 30 to 35 years.They are working active but don't have maternity activities. The results of this longitudinal investigation show that women who takes any activity are better than non active women. We find diference in circular dimension, sfin fold, % body fat and BMI.